ACQUISITION OF AGRICULTURAL LAND - Trgovčević Prokić, Milena; Počuča, Milan (Economics of Agriculture, 2016)
The expropriation is a forced deprivation of property in the public interest, and represents a form of restriction of property rights. The core issue of expropriation is a expropriated real estate. In determining fair monetary compensation, it is necessary to fnd criteria which protect both sides and fnd a balance and proportionality between social and individual interests. In the procedure of question of the just monetary compensation to the owner of the determining the compensation for the expropriated property the court has a duty to determine fair monetary compensation so that there is no unjust enrichment of the owners of the real estate and the impoverishment of the user of the expropriated property or vice versa. This paper analyzes the rules by which it is acted upon when there is a need to expropriate and determine a fair monetary compensation that should belong to the owner of the expropriated real estate.